Some Trigonometric Formulae for the Interpretation of Continuous Seismic Profiles - Brooks, M. (The International Hydrographic Review, 2015)
Methods are discussed for the calculation of depth and dip of subbottom reflectors in seismic profiles. An example is given of a convenient form of interpretation table based on the formulae of Curry et al. (1965), for use when the horizontal separation of acoustic source and hydrophone array is significant. For the case where the horizontal separation of source and receiver is negligible, simple formulae are presented which facilitate the calculation of reflector dip. Following a discussion of the calculation of apparent dip along the profile direction, methods are outlined for the computation of true dip at profile intersection points.